On k-Type 2-Degenerate Slant Helices in 4-Dimensional Minkowski Space-Time - Yuzbasi, Zuhal Kucukarslan; Yilmaz, Munevver Yildirim (Amer Scientific Publishers, 2018)
In this study, our aim is to introduce for k is an element of {0, 1, 2, 3} the notion of k-type 2-degenerate slant helices in 4-dimensional Lorentz-Minkowski space-time M-1(4). We prove some characterizations in terms of the curvatures of the curves and give k-type 2-degenerate slant helices lying on a pseudo-sphere S-1(3)(r) with radius r > 0.
Keywords: 2-Degenerate Curve; k-Type 2-Degenerate Slant Helix; Pseudo-Sphere; Minkowski Space-Time